Analysis of the Economic Impact of Mass Immigration in the Light of German Data - Tatay, Tibor; Bándy, Katalin (Public Finance Quarterly, 2020)
Many welcomed the mass immigration of 2015 from an economic approach in Germany. Immigrants were seen as the solution to the German labor shortage and the potential to improve the expected deterioration of public finances as a result of demographic trends. As German integration policy has become a kind of standard in the European Union, we have examined the economic consequences of mass immigration. Looking at the German intergenerational balance sheet, immigration appears to improve the sustainability of public finances if a high proportion of immigrants obtain the same qualifications as the autochthonous German population. Also, access to the labor market will only be achieved if the right level of qualification is obtained. Empirical evidences show that the qualification level of even the second- and third-generation immigrants does not reach that of the native Germans. Unemployment among them is above the German average. The actual data indicate that negative scenarios are likely to take place for newcomers, i.e. they probably will not meet the requirements of the German labor market and will not improve the long-term sustainability of German public finances.